Beneficiaries’ Expectations and Return on Pension Fund Investment in Nigeria - Babatunde A. AGBEYANGI; Rafiu O. SALAWU; Samuel A. FAKILE; Olubukola UWUIGBE (Communications of International Proceedings, 2020)
The study examines beneficiaries’ expectation in relation to returns generated from pension fund investment in Nigeria. This study investigates the perceptions of contributors of pension fund from the various investments by Pension fund administrators (PFA). The study adopted survey design method using questionnaire to establish the expectations of pension fund beneficiaries on the returns generated on their contributions. The population of the study consists of active pension contributors, retirees of Federal and State Polytechnics in the South-Western state of Nigeria, PFAs and Pension Fund Custodians staff respectively totaling 13,528. Sample size of 389 was drawn using Taro Yamane method of sample size selection technique on margin of error of 5%, where 98.7% of the entire research instrument was returned. Data collected were analyzed using both descriptive and inferential statistics. The descriptive statistics consists of mean and standard deviation while Kruskal Wallis test, a non-parametric test for mean difference in response approach was used to infer. The study concluded that expectations vary from beneficiary to beneficiary but, with general expectation of reasonable returns on investment of their contributions by pension fund managers. The study therefore, recommend that pension managers should, as a matter of diligence, invest pension funds into portfolio that will make for stable value of pension for contributors at retirement.
Keywords: Beneficiaries’ expectation; Pension fund investment; Pension fund administrators; Return on investment.